1998
DOI: 10.1016/s0893-133x(98)00040-2
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Administration of Fluoxetine Impairs Estrous Behavior in Intact Female Rats

Abstract: Treatment with serotonin reuptake inhibitors (SRIs) has been shown to cause reduced libido and anorgasmia in women.A large body of evidence suggests that serotonin may influence sexual behavior in estradiol ϩ progesterone primed, gonadectomized female rats; however, the influence of selective SRIs on the estrous behavior of intact female rats has not been described previously. In the present study, the effect of 1 to 3 weeks of fluoxetine administration (10 mg/kg daily) on vaginal and behavioral estrus in inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
52
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 39 publications
6
52
3
Order By: Relevance
“…Marvan and co-workers (Marian et al 1996) have thus previously reported that the immobility displayed by female rats in a so-called animal model of depression (the swimming immobility test) is more pronounced in the diestrus phase than in the estrus phase of the cycle, and that the immobility in the diestrus phase is reduced by treatment with a serotonin reuptake inhibitor, clomipramine. Tentatively, serotonin may be a key factor in mediating the effects of cycle-related changes in hormonal levels on various aspects of behavior; supporting this notion, we recently showed that administration of a serotonin reuptake inhibitor reduces sexual receptivity in the estrus phase of normally cycling, female rats (Matuszczyk et al 1998; see also Uphouse et al 1991).A few technical comments are warranted. Albert and co-workers (1991) have reported that aggressive behavior is exaggerated in female rats that have experienced pseudopregnancy; for this reason, the rats used in the first and second experiments had all been the subjects of one period of pseudopregnancy before the resident intruder experiments were started.…”
mentioning
confidence: 70%
“…Marvan and co-workers (Marian et al 1996) have thus previously reported that the immobility displayed by female rats in a so-called animal model of depression (the swimming immobility test) is more pronounced in the diestrus phase than in the estrus phase of the cycle, and that the immobility in the diestrus phase is reduced by treatment with a serotonin reuptake inhibitor, clomipramine. Tentatively, serotonin may be a key factor in mediating the effects of cycle-related changes in hormonal levels on various aspects of behavior; supporting this notion, we recently showed that administration of a serotonin reuptake inhibitor reduces sexual receptivity in the estrus phase of normally cycling, female rats (Matuszczyk et al 1998; see also Uphouse et al 1991).A few technical comments are warranted. Albert and co-workers (1991) have reported that aggressive behavior is exaggerated in female rats that have experienced pseudopregnancy; for this reason, the rats used in the first and second experiments had all been the subjects of one period of pseudopregnancy before the resident intruder experiments were started.…”
mentioning
confidence: 70%
“…Although fluoxetine has been previously studied in ovariectomized females primed with estrogen and/or progesterone, the results have been equivocal [10,25]. In one report, ovariectomized rats were treated with 10 mg/kg fluoxetine for as long as 42 days [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although fluoxetine has been previously studied in ovariectomized females primed with estrogen and/or progesterone, the results have been equivocal [10,25]. In one report, ovariectomized rats were treated with 10 mg/kg fluoxetine for as long as 42 days [25]. At weekly intervals, females were hormonally primed with estrogen and progesterone and tested for sexual receptivity (measured by the lordosis reflex) and sexual motivation (measured by the percentage of time females spent in the vicinity of a male).…”
Section: Introductionmentioning
confidence: 99%
“…Disruptive effects of 5-HT on female reproduction are well recognized [37,50,56,67]. In addition, several of the effects of fluoxetine (in particular, reduced food intake [3,4,6,23] and activation of the hypothalamic-pituitary-adrenal (HPA) axis [54,68]) might be anticipated to substantially alter the neuroendocrine system and thereby influence the female's reproductive cycle [2,7,26,27,29,53,69].However, in a report by Matuszczyk et al [35], sexual behavior and vaginal cyclicity of female rats were examined during 3 weeks of treatment with 10 mg/kg fluoxetine [35]. Fluoxetine reduced sexual behavior, but had no disruptive effect on the female's vaginal cycle.…”
mentioning
confidence: 99%
“…This was a significant observation since it had been generally assumed that fluoxetine-induced female sexual dysfunction occurred independent of drug-induced modification of the HPG axis controlling estrous cyclicity. According to the NTP-CERHR Expert Panel Report in 2004, "The data in female rats are sufficient to qualitatively demonstrate that fluoxetine treatment with 10 mg/kg bw/day by s.c. or i.p injection results in altered estrous behavior and sexual receptivity, but has no effect on estrous cycle length" [25].Since concurrent vaginal and behavioral estrus have been examined in only two reports [35,63], it is important to identify explanations for the contrasting findings. In the following manuscript, we investigate one such potentially important difference between the two studies.…”
mentioning
confidence: 99%